2013
DOI: 10.3389/fpls.2013.00162
|View full text |Cite
|
Sign up to set email alerts
|

Efficient selection and evaluation of transgenic lines of Crambe abyssinica

Abstract: Crambe abyssinica is a dedicated oilseed crop suitable for production of industrial feedstocks. Genetic modification of crambe has progressed substantially in the last few years, but the transformation efficiency needs to be further improved. Meanwhile, developing a reliable molecular system including Southern blot and qRT-PCR analyses is desired for effectively evaluating transgenic lines and gene expression levels of both endogenous and transgenes. In this study, we have developed an efficient transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Residual genomic DNA was removed through DNase treatment using TURBO DNA-free (Ambion, Austin, TX). First-strand cDNA was synthesized according to Li et al (2013) using RevertAid H Minus First Strand cDNA Synthesis Kit (Fermentas, St. Leon-Rot, Germany). The cDNA was diluted 4 x, and 2 lL was used for 20-lL qRT-PCR using Applied Biosystems 7300 Real-Time PCR System (Applied Biosystems, Foster City, CA) with Platinum SYBR Green qPCR SuperMix-UDG module (Invitrogen, Carlsbad, CA).…”
Section: Quantitative Real-time Pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…Residual genomic DNA was removed through DNase treatment using TURBO DNA-free (Ambion, Austin, TX). First-strand cDNA was synthesized according to Li et al (2013) using RevertAid H Minus First Strand cDNA Synthesis Kit (Fermentas, St. Leon-Rot, Germany). The cDNA was diluted 4 x, and 2 lL was used for 20-lL qRT-PCR using Applied Biosystems 7300 Real-Time PCR System (Applied Biosystems, Foster City, CA) with Platinum SYBR Green qPCR SuperMix-UDG module (Invitrogen, Carlsbad, CA).…”
Section: Quantitative Real-time Pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…Later it was reported that adding various thiol compounds in the co-cultivation medium significantly increased the transformation efficiency of soybean (Olhoft and Somers, 2001; Olhoft et al, 2001; Zeng et al, 2004). In crambe, ( Crambe abyssinica ), it was reported that the transformation efficiency was similar when transformants were exposed to either constant low selection pressure (continuously on 3 mg/l hygromycin) or exposed to higher concentration and followed by lower selection concentration (started by 10 mg/l and followed by 3 mg/l of hygromycin; Li et al, 2013). This observation is in contradiction to many reports where higher transformation efficiency is obtained by gradually increasing the selection agent from low to higher concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Crambe has some good agronomic properties, such as potential for phytoremediation of heavy metal contaminated soils and sediments (Chhikara et al, 2012) and tolerance to abiotic stress such as reduction of soil nematodes, which make it easily accepted by commercial production after improvement (Li et al, 2013). The weed control on crambe is important, such as in any other agricultural species, for the success of the activity.…”
Section: Introductionmentioning
confidence: 99%